2006
DOI: 10.1128/iai.01151-06
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Peptide Containing Minimal T- and B-Cell Epitopes ofPlasmodium falciparumCircumsporozoite Protein Elicits Protection against Transgenic Sporozoite Challenge

Abstract: An effective malaria vaccine is needed to address the public health tragedy resulting from the high levels of morbidity and mortality caused by Plasmodium parasites. The first protective immune mechanism identified in the irradiated sporozoite vaccine, the "gold standard" for malaria preerythrocytic vaccines, was sporozoiteneutralizing antibody specific for the repeat region of the surface circumsporozoite ( There is a critical need for an effective malaria vaccine, as standard public health measures have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 70 publications
5
54
1
Order By: Relevance
“…The P. falciparum RTS,S vaccine candidate has been constructed with sequences representing the R and the C region of the P. falciparum CS 2 known to contain strong B-and T-cell epitopes, respectively. 33 Apparently, for the RTS,S construct the N region of that protein was not considered important; however, in the case of P. vivax we have evidence to believe that the N fragment has greater vaccine potential. 34 The high immunogenicity displayed by the N region of the CS here, is in agreement with previous serological studies performed before, not only with P. vivax 35 but more recently also with P. falciparum , 36 where the N region induced better immunogenicity under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The P. falciparum RTS,S vaccine candidate has been constructed with sequences representing the R and the C region of the P. falciparum CS 2 known to contain strong B-and T-cell epitopes, respectively. 33 Apparently, for the RTS,S construct the N region of that protein was not considered important; however, in the case of P. vivax we have evidence to believe that the N fragment has greater vaccine potential. 34 The high immunogenicity displayed by the N region of the CS here, is in agreement with previous serological studies performed before, not only with P. vivax 35 but more recently also with P. falciparum , 36 where the N region induced better immunogenicity under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to measure PfCSP-specific humoral immune response, ELISA assay was done as described above, except that ELISA plates were coated with 1 μg/ml (T1B)4 peptide that contains NANP repeat sequence (31). (T1B)4 peptide was provided by Elizabeth Nardin, New York University School of Medicine, New York, New York, USA.…”
Section: Figurementioning
confidence: 99%
“…Through the use of transgenic rodent parasites, it has become possible to quantify infectivity, as well as delineate humoral and cellular immune responses that are critical in anti-CS immunity (10,17). The use of the CS(Pf) transgenic parasites has also demonstrated that linear peptides such as those described above need to be further explored for their potential as vaccines (6). Further vaccine immunogenicity and CS(Pf) sporozoite challenge studies can also help in dissecting the potential roles of various arms of cellular immune responses.…”
Section: Transgenic Parasites Based On Sporozoite Antigen Csmentioning
confidence: 99%
“…The findings from this in vivo assay further substantiate the potential of CS-based target antigens to induce either sterile or protective immunity against sporozoite challenge. Other formulations of CS vaccines have also been tested and protective epitopes from linear synthetic peptides containing minimal B-and T-cell epitopes of PfCS have been examined using CS(Pf) in a murine model (6). Peptides containing CS B-and T-cell epitopes were immunogenic in mice and elicited antibodies neutralizing sporozoites of the CS(Pf) parasites (6), suggesting that preerythrocytic vaccine development can benefit from transgenic parasites in murine models.…”
Section: Transgenic Parasites Based On Sporozoite Antigen Csmentioning
confidence: 99%
See 1 more Smart Citation